Service quality perceptions and patient satisfaction: a study of hospitals in a developing country - Andaleeb, Syed Saad (© 2001 Elsevier Science Ltd., 2016)
This article was published in the Social Science & Medicine [© 2001 Elsevier Science Ltd.] and the definite version is available at: http://doi.org/10.1016/S0277-9536(00)00235-5 The Journal's website is at: http://www.sciencedirect.com/science/article/pii/S0277953600002355